Komodifikasi Agama sebagai Identitas Kesalehan Sosial - Zailani, Muh Rizki; Ulinnuha, Roma (Jurnal Riset Agama, 2023)
The purpose of this research is to identify and analyze the commodification of religion used as an identity of social piety in this modern era. In order to reveal the phenomenon of this religious commodification pattern, the researcher uses a normative qualitative method approach based on library research by using secondary data such as previous journal articles, books, proceedings and similar sources as the main data. From the research conducted, it was found that there are at least five patterns in the phenomenon of religious commodification. First, by branding products and services with Islamic and modern nuances. Second, offering facilities that make it easier for Muslims to worship even at an above-standard cost. Third, limiting activities that are considered un-Islamic as a form of Islamic service. Fourth, displaying Islamic symbols as a sign that the product is an Islamic product. Fifth, framing in the media and promotions that by buying or consuming these products or services, it is considered to comply with Islamic teachings.